Review of key vertical-cavity laser and modulator advances enabled by advanced MBE technology - Coldren, Larry A. (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films, 2021)
In this special issue honoring Professor Arthur Gossard, I am delighted to be able to review a small segment of the work he has enabled while at UCSB on the subject of the title, but further limited to devices grown all-epitaxially. When he arrived in 1987 from Bell Labs, he had already been consulting on the installation of our new Gen-II MBE that we intended to use for vertical-cavity Fabry–Pérot modulators, devices somewhat similar to those he had grown at Bell Labs. However, within a couple of years, we obtained leading results on reflection modulators, moving the on/off contrast from prior values of less than 5:1 to more than 50:1 with insertion losses of less than 2 dB, required voltages in the 2–4 V range, and changes in reflection per volt to ∼20%/V. These had multiple-quantum-well (MQW) active regions to phase shift and partially absorb the resonant lightwaves within a cavity formed between two distributed-Bragg-reflector (DBR) mirrors all formed in the AlGaAs/GaAs system. Also in this same period, novel vertical-cavity surface-emitting laser (VCSEL) structures analogous to the modulators were developed. They had strained InGaAs/GaAs MQW actives and AlGaAs/GaAs DBRs and operated near 980 nm. The initial new idea was to place active quantum wells only at the maxima of the cavity E-field standing wave, which provides nearly a doubling of the modal gain they contribute. These designs quickly led to leading results in threshold current (<1 kA/cm2—1990 and Ith < 1 mA with Po > 1 mW—1991), power out (up to 113 mW cw—1993), and temperature stability with gain offset (constant output over 50 °C—1993). Additional notable results in the 1990s included a selective oxidation of AlGaAs to form lens-like intra-cavity apertures for dramatic reductions in optical cavity loss; the first strained layer InGaAlAs/GaAs 850 nm VCSELs; and an 8-wavelength division multiplexing VCSEL array integrated within a 60 μm diameter for direct emission into a multimode fiber. In the 2000s, results included all-epitaxially grown 1310 nm and 1550 nm VCSELs that employed AlGaAsSb DBRs and AlGaInAs actives with tunnel junctions to enable two n-type contacts on InP for low thermal and electrical resistance; multi-terminal VCSELs for polarization modulation to double the information output on a single optical beam; and a novel high-speed, high-efficiency design that incorporated sophisticated bandgap engineering in the DBRs and carbon doping for low optical loss and electrical resistance, midlevel Al-content mirror layers near the cavity for deep oxidation to reduce capacitance, and a redesigned lens-like aperture for reduced mode volume. This latter design gave record modulation bandwidth and efficiency results then, and it is still being used around the world for the leading results today. In the most recent decade, InGaAsSb/AlGaAsSb/GaSb materials for VCSELs and photonic ICs have been studied for emission in the 2–4 μm wavelength range.